Asas Kepastian Hukum Dalam Penyelenggaraan Pemerintahan Desa - Arifin Wahyuono; Arum Sabil; Mohammad Aris; Ahmad Nasikin (JURNAL RECHTENS, 2025)
This study aims to analyze how village governance is implemented based on legal certainty in Law Number 6 of 2014 concerning Villages. This study uses a normative legal research method with a legislative approach and a conceptual approach. The conclusion obtained is that the principle of legal certainty is one of the fundamental principles in village governance. All government, development, and community empowerment activities must be carried out in accordance with applicable laws and regulations. The application of the principle of legal certainty in village governance is seen in the preparation and implementation of village regulations and in the administrative aspects of village governance. By implementing the principle of legal certainty, village governance can realize good governance, is able to provide legal protection for village officials, village communities receive assurance that government administration runs in an orderly, transparent, and non-arbitrary manner, and also strengthens public trust in the village government.